Predictors of voting behavior & support towards Malaysian leaders: A study among factory workers in Malaysia - Tengku Mohd Azzman, Tengku Siti Aisha; A Manaf, Aini Maznina; Ahmad, Zeti Azreen; Yusoh, Mohd Helmi (2019)
Factory workers are a relatively understudied and marginalized population, although they are one of the biggest contributors to the Malaysian labor force. This study aimed to focus on factory workers, and factors that influenced their voting behavior and support towards Malaysian leaders, such as age, gender, education level and income. A cross-sectional survey was carried out among factory workers in Malaysia, mainly in the industrial areas in Klang Valleys (N = 475). Generally, Malaysian factory workers are politically active; majority reported that they have registered as voters (88%) and did vote in the previous General Election in 2018 (82%). Findings also indicate that due to the recent General Election in 2018, support for political parties did reflect the changes seen recently in the Malaysian political landscape, where almost half of the factory workers were seen to choose Pakatan Harapan (42%) as their party of choice. More interesting was the fact that the votes among Malay workers were split almost evenly between three parties: PH, UMNO and PAS. Factory workers also mainly had positive perception towards the top Malaysian leaders (i.e. PM and DPM), although they were more ambivalent towards other leaders. Overall, it is found that while gender did not influence voting behavior, age group, income group, and education level did influence whether factory workers chose to vote or not. Thus, in order to increase support for political parties and to ensure factory workers vote, communication strategies should be tailored to attract voters from this demographic group.